TEENAGERS' PERCEPTIONS ABOUT CAREER CHOICES AND CAREER PROSPECTS - Zuhra Mirzotilloyevna Radjabova (European Science Publishing, 2024)
The right choice of profession is the main criterion that determines the efficiency of professional activity. Because identifying the need for a profession allows for the correct formation of motivations for activity. There is a direct connection between the proportion of adolescents to the profession and their perceptions of the professional perspective and professional formation.
Keywords: Career choice, questionnaire, consciousness, professional maturity, imagination, adolescent, socio-psychological character, career guidance, success.